Cumulative Damage Evaluation of RC Bridge Piers subjected to Multiple Earthquakes - Do Hyung Lee; Byeong Hwa Kim; Jung Joong Kim; WooSeok Kim (Shock and Vibration)
Successive earthquakes of Kocaeli and Duzce within three months indicated that even the survived lifeline structures such as bridges under the former event may have damage or collapse potential under the latter event due to their possible stiffness degradation. It is thus important that a rigorous seismic analysis of such structures should account for the effect of prior earthquake damage. For this purpose, nonlinear seismic analysis of a reinforced concrete bridge structure has been carried out under both single and multiple earthquake ground motions. Behavior and response evaluation of the bridge piers subjected to such motions have been discussed in terms of using both flexure-axial and flexure-shear-axial interaction models. Analytical results show that the stiffness degradation under multiple earthquake ground motions is more pronounced than that under single earthquake ground motion. In addition, comparison of the response without and with shear demonstrates that shear deformation is of significance. The response with shear exhibits the increase in displacement demand and decrease in lateral force carrying capacity, leading to a decrease in energy dissipation capacity. It is concluded that seismic analysis of reinforced concrete bridge structure should account for the effect of multiple earthquake ground motions to assess the demand on such structure properly.